Strategi Pemasaran dan Adaptasi Digital Produk Tabungan Emas di Pegadaian Syariah Kudus (Jurnal Ekonomi dan Bisnis Islam, 2025)
AbstractThis study aims to analyze the marketing strategy and digital adaptation of gold savings products at Pegadaian Syariah Kudus Regency, with the goal of increasing customer numbers and fostering long-term relationships with consumers. Motivated by the significant growth of the Islamic financial industry and stable public interest in gold investment, the study employed a qualitative approach, utilizing field methods that included observation, in-depth interviews, and documentation. The results of the study revealed the implementation of the 7P marketing mix (product, price, place, promotion, people, process, and physical evidence). Digital adaptation through the Pegadaian Syariah Digital Service (PSDS) application provided added value in the form of easy access, supported by comprehensive digital education for various customer segments. Important findings show the success of the inclusive pricing strategy with a minimum deposit of IDR 15,000 and the active involvement of all employees in marketing activities. The main challenges include limited public understanding of gold savings products, limited perceptions of pawnshop services, and technical obstacles in digital implementation. Effective solutions implemented include a personal approach, expanding socialization, technical assistance, and ongoing digital education. In conclusion, the integration of relationship marketing strategies with digital adaptation that focuses on customer education has proven effective in increasing the number of customers and the competitiveness of Pegadaian Syariah Kudus Unit in the sharia financial industry.Keywords: Relationship Marketing; Gold Savings; Sharia Pawnshop; Digital Adaptation; Customer Education. AbstrakPenelitian ini bertujuan untuk menganalisis strategi pemasaran dan adaptasi digital produk tabungan emas di Pegadaian Syariah Kabupaten Kudus dalam upaya meningkatkan jumlah nasabah dan membangun hubungan jangka panjang dengan konsumen. Dilatarbelakangi oleh pertumbuhan signifikan industri keuangan syariah dan minat masyarakat terhadap investasi emas yang stabil, penelitian menggunakan pendekatan kualitatif dengan metode lapangan melalui observasi, wawancara mendalam, dan dokumentasi. Hasil penelitian mengungkapkan implementasi bauran pemasaran 7P (produk, harga, tempat, promosi, orang, proses, dan bukti fisik). Adaptasi digital melalui aplikasi Pegadaian Syariah Digital Service (PSDS) memberikan nilai tambah berupa kemudahan akses, didukung edukasi digital yang komprehensif untuk berbagai segmen nasabah. Temuan penting memperlihatkan keberhasilan strategi penetapan harga inklusif dengan setoran minimal Rp15.000,00 serta keterlibatan aktif seluruh karyawan dalam kegiatan pemasaran. Tantangan utama meliputi keterbatasan pemahaman masyarakat tentang produk tabungan emas, persepsi terbatas tentang layanan pegadaian, serta kendala teknis dalam implementasi digital. Solusi efektif yang diterapkan mencakup pendekatan personal, perluasan sosialisasi, bantuan teknis, dan edukasi digital berkelanjutan. Kesimpulannya, integrasi strategi pemasaran relasional dengan adaptasi digital yang berfokus pada edukasi nasabah terbukti efektif meningkatkan jumlah nasabah dan daya saing Pegadaian Syariah Unit Kudus di industri keuangan syariah.Kata Kunci: Relationship Marketing; Tabungan Emas; Pegadaian Syariah; Adaptasi Digital; Edukasi Nasabah.